100 μm‐Order Patterning of Organic Semiconductor Layers Using a Thermally Converted Precursor Technique and its Application to Organic Light Emitting Diodes. Issue 2 (8th November 2013) - Goto, Daisuke; Mohri, Masataka; Morimoto, Kei; Mzhavia, Aleksandre; Adachi, Chihaya
<x xml:space="preserve">Abstract</x> An N, N′‐di(naphthalenyl)‐N, N′‐di(naphthalen‐2‐yl)‐benzidine (α, β‐TNB) precursor is prepared that can be thermally converted into α, β‐TNB, losing its solubilizing groups to produce an insoluble component in isopropanol. Narrow pixel arrays with widths of 100‐180 μm are then formed by thermal conversion of the α, β‐TNB precursor, providing an OLED performance comparable to those made by vacuum deposition. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>